Dose‐dependent inhibitory effects of proton pump inhibitors on human osteoclastic and osteoblastic cell activity. (5th September 2013) - Costa‐Rodrigues, João; Reis, Sara; Teixeira, Sónia; Lopes, Sandra; Fernandes, Maria H.
<x xml:space="preserve">Abstract</x> Proton pump inhibitors (PPIs), a class of molecules that are used to decrease gastric acid production, might have adverse effects on bone metabolism. The aim of this study was to characterize the concentration‐dependent and time‐dependent effects of three PPIs (omeprazole, esomeprazole, and lansoprazole) on human osteoclast precursor cells isolated from peripheral blood, and on human mesenchymal stem cells (osteoblast precursors). Cell cultures were characterized for total protein content, apoptosis, and several osteoclastic/osteoblastic features, and also for the involvement of some intracellular signaling pathways. PPIs caused a dose‐dependent decrease in cellular density, which correlated with an increase in the apoptosis rate, effects that became statistically significant at concentrations ≥ 10−5 m. They also inhibited phenotype‐related gene expression and functional parameters. For both cell types, cellular function, i.e. osteoclastic resorption and the formation of mineralized deposits by osteoblastic cells, was more affected than proliferation‐related parameters. The three PPIs showed similar qualitative and quantitative effects, but displayed some differences in the underlying intracellular signaling pathways. These results suggest that PPIs might have a direct deleterious effect on bone cells, with the possibility of decreased bone turnover.